PENYULUHAN MENGENAI KEAMANAN DAN KEBENARAN INFORMASI DIGITAL SAAT PANDEMIK COVID-19 - Adikara, Fransiskus; Sandfreni, Sandfreni; Alam, Putra Fajar (Universitas Esa Unggul, 2020)
Implementation of Community Service in the context of the Scientific Forum of Lecturers conducted jointly with the Research and Community Service Institute, Esa Unggul University, West Jakarta. This outreach program is intended for lecturers, educators, and other general participants who aim to share knowledge or transfer knowledge about the security and truth of digital information in today's special era during the Covid-19 pandemic. With this activity, the specific target to be achieved is so that participants can understand the concept of digital information security and be able to understand the truth of digital information that is currently circulating a lot. With this knowledge and understanding, especially for participants who are unfamiliar with digital technology, which in this pandemic period must follow the development of technology, it is hoped that they will gain the ability to maintain the security and correctness of their information. The method used is in the form of counseling with practical delivery through knowledge transfer and presentation of features and practical examples delivered online through a webinar event using the Zoom method. After the webinar event was finished, the participants filled out a questionnaire to get a conclusion on the knowledge transfer that had been carried out.Ã‚Â Keywords :digital information security, truth of digital information security, covid-19